I see, but that makes it confusing for me. That's why i don't understand what to do.
I'll take a shot at this.
-6n = (n+1)(n+2)...so-so?? I can see that this problem can be figured out, but I can't find the correct numbers... HELP ME. Omg, i can't find a number that will fit in with all the problems. I think n is around 8 in this one. But i can't figure it out.
-6n = (n-1)(n-2)...Works. Because:
-6 x -2 = 12 (-3) x (-4) = 12. (Lacey showed me this solution eariler)
-6n(n-2) = (n-1)(n) This can't possibly work. You can always prove me wrong though if you like. But you will never even get a close answer because the first equation will have a HIGH total. And the second equation will always be lower. SO, screw this one for now.
-6n(n+2) = (n+1)(n) Screw this one too.
Well, that's as far as i got. What do i need to do next to progress?